Prevalence and risk factors for central sleep apnea in infants with laryngomalacia - Archwin Tanphaichitr (2018)
Objective. To identify the prevalence of and risk factors for central sleep apnea (CSA) in infants who are diagnosed with laryngomalacia. Study Design. Case series with chart review. Setting. Quaternary care pediatric hospital. Subjects and Methods. We performed a chart review in infants with laryngomalacia. All infants had diagnostic polysomnography (PSG) performed from 2003 to 2012. Infants who underwent supraglottoplasty or other upper airway surgery prior to PSG were excluded. CSA was defined as central apnea index 5. Demographic data, underlying diseases, and PSG data were reviewed and analyzed. Results. Fifty-four patients met the inclusion criteria. The mean age at the date PSG was performed was 3.4 ± 2.7 months. The prevalence of CSA in infants with laryngomalacia was 46.3%. Odds ratio (OR) of CSA was above 2.0 in patients with the following risk factors: underlying neurologic disease, hypotonia, or syndrome (OR = 2.5, P = .13), history of apparent life-threatening events (OR = 2.7, P = .19), premature infants (OR = 2.2, P = .33), and age less than 3 months (OR = 2.3, P = .15). However, none of the risk factors were statistically significant. Analysis of sleep architecture revealed a decrease in total sleep time (345.4 ± 70.6 minutes vs 393.5 ± 68.3 minutes, P = .02) and sleep efficiency (67.7 ± 8.9% vs 75.2 ± 9.3%, P = .004) in the CSA group. Conclusion. CSA is relatively common in infants with laryngomalacia. There seems to be a higher prevalence of CSA in infants with certain risk factors, but none of the risk factors are statistically significant. The presence of CSA can lead to alteration in sleep architecture. In addition to clinical evaluation, polysomnography may be warranted for the evaluation of infants with laryngomalacia and associated complex medical conditions. © American Academy of Otolaryngology-Head and Neck Surgery Foundation 2014.